STRATEGI PROGRAM GERAKAN MASYARAKAT GEMAR MEMBACA (GEMA ARCA) DALAM MENINGKATKAN MINAT BACA DI KABUPATEN KLUNGKUNG - Oktariani, Ni Putu Eva; Prabawati, Ni Putu Anik; Yudartha, I Putu Dharmanu (CITIZEN CHARTER, 2020)
ABSTRACT The library sector has high potential in creating quality human resources. In realizing this, the government needs to increase the reading interest the still low Klungkung societyaby utilizingathealibrary. The purpose of this research is to identify the implementation of the Gema Arcaastrategy in expanding the reading interest of the Klungkungasocietyaandaeffortsatoadesignaa newaapproach.aTheaunitaof analysis of this research was Archieves and Library Office of Klungkung Regency and this research used a qualitative descriptive method. The study produces alternative strategy of SO5(Strengths-Opportunities) through the SWOT matrix test, namely : utilizing IT as a means of information in the Klungkung regional library, develop appeal throughalibrary collections, create new innovations inathe implementation of library services, and procurementaof infrastructure facilitiesato supportalibrary services,aas well increasingaschoolaand village library development. Keyword : Strategy, Reading SocietyaMovementa(GemaaArca), ReadingaInterest.